Loaning Ships and Leveraging Influence? American and British Responses to the HMAS Voyager Tragedy. Issue 4 (8th July 2021) - Paget, Steven
Abstract: The loss of HMAS Voyager following a collision with HMAS Melbourne on 10 February 1964 was a national tragedy for Australia. Britain and the United States were quick to express their sympathy and both offered to loan a ship to the Royal Australian Navy (RAN) to offset their loss. The offers were genuine and were intended to aid an important partner. The RAN had been tied closely to the RN since its creation, but the 1950s and 1960s witnessed an important transition and the RAN's decision to purchase the American designed and built Charles F. Adams class destroyer as its new class of escorts in 1961 exemplified an increasing alignment with the United States Navy (USN). The Voyager tragedy reignited the debate over standardization and afforded both the Royal Navy (RN) and USN with an opportunity to attempt to strengthen ties with the RAN. The eventual Australian decision to accept the British offer, ultimately, had little effect on the development of the RAN. Rather than harking back to a time when the RAN was an appendage of the RN, the decision to select the British ship was a mark of its increasing independence.